Corrigendum: Open Social Scholarship Annotated Bibliography - El Khatib, Randa; Seatter, Lindsey; El Hajj, Tracey; Leibel, Conrad; Arbuckle, Alyssa; Siemens, Ray; Winter, Caroline (KULA)

(untitled) (University of Victoria Libraries, 2020)
Following the publication of our recent article in KULA: Knowledge Creation, Dissemination, and Preservation Studies (https://kula.uvic.ca/articles/10.5334/kula.58/), we wish to bring the following corrigendum to your attention.